2010
DOI: 10.2217/fon.09.174
|View full text |Cite
|
Sign up to set email alerts
|

AMPK As a Metabolic Tumor Suppressor: Control of Metabolism and Cell Growth

Abstract: AMPK is an evolutionarily conserved fuel-sensing enzyme that is activated in shortage of energy and suppressed in its surfeit. AMPK activation stimulates fatty acid oxidation, enhances insulin sensitivity, alleviates hyperglycemia and hyperlipidemia, and inhibits proinflammatory changes. Thus, AMPK is a well-received therapeutic target for metabolic syndrome and Type 2 diabetes. Recent studies indicate that AMPK plays a role in linking metabolic syndrome and cancer. AMPK is an essential mediator of the tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
320
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(328 citation statements)
references
References 125 publications
(142 reference statements)
4
320
0
4
Order By: Relevance
“…Although autophagy is primarily a process for the cell protection, it can also play a role in cell death (Mizushima et al, 2008). It has been shown that a number of tumor suppressors can promote autophagy, such as LKB1 (Liang et al, 2007) , TSC (Zhou et al, 2009), DAP kinase (Bialik and Kimchi, 2010), PTEN (Errafiy et al, 2013), UVRAG (ultraviolet radiation resistanceassociated gene) (Liang et al, 2006) and AMPK (Luo et al, 2010). Interestingly, autophagy in TMZ-resistant glioblastoma cells cannot be induced by TMZ while the combination of VPA and TMZ can enhance autophagic cell death in TMZ-resistant glioma cells (Ryu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although autophagy is primarily a process for the cell protection, it can also play a role in cell death (Mizushima et al, 2008). It has been shown that a number of tumor suppressors can promote autophagy, such as LKB1 (Liang et al, 2007) , TSC (Zhou et al, 2009), DAP kinase (Bialik and Kimchi, 2010), PTEN (Errafiy et al, 2013), UVRAG (ultraviolet radiation resistanceassociated gene) (Liang et al, 2006) and AMPK (Luo et al, 2010). Interestingly, autophagy in TMZ-resistant glioblastoma cells cannot be induced by TMZ while the combination of VPA and TMZ can enhance autophagic cell death in TMZ-resistant glioma cells (Ryu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This gene was later found to be a target for mutational inactivation in human malignancies including non-small cell lung carcinoma (Sanchez-Cespedes et al, 2002;Carretero et al, 2004;Ji et al, 2007;Matsumoto et al, 2007;Makowski and Hayes, 2008;Komiya et al, 2010;Mahoney et al, 2009), cervical carcinoma (Wingo et al, 2009), melanoma (Guldberg et al, 1999;Rowan et al, 1999) and others (Sanchez-Cespedes, 2007). The LKB1 gene encodes a serine/threonine kinase essential for the activation of AMPK (AMP-activated protein kinase) and 12 AMPK-related kinases; thus, it regulates multiple signaling pathways in cell growth, cell polarity and metabolism (Hezel and Bardeesy, 2008;Shackelford and Shaw, 2009;Luo et al, 2010). Currently, information regarding the exact roles and mechanisms underlying LKB1-mediating tumor suppression remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition to these well-characterized functions in metabolic syndromes, AMPK serves as a metabolic tumor suppressor that reprograms the cellular metabolism and elicits a metabolic checkpoint on the cell cycle through its actions on mTORC1, p53, and other modulators for cell proliferation, cell growth, cell survival, and autophagy. 12 Further, LKB1 activates AMPK and represses RNA synthesis. 13 In LKB1-deficient lung cancer cells, AMPK activity is suppressed, leading to increased cell growth, whereas the ability of AMPK to inhibit cell growth is restored when wild-type LKB1 is expressed.…”
mentioning
confidence: 99%